Paul Virilio: Clinical Theory - Jim Morrow; Rob Shields (Media Theory)
We characterize Paul Virilio as a «clinical» thinker who diagnoses systemic problems of modernity in accidents and unusual incidents. Virilio’s method of clinical theoretical diagnosis is illustrated through an examination of common elements in his writing, including the German ‘Atlantic Wall’ fortifications of the Second World War, the Svalbard Global Seed Vault, consumers’ widespread use of household products emitting volatile organic compounds (VOCs), and the global leisure tourism industry. All illustrate an apocalyptic thinking and a legacy of catastrophe that Virilio refers to as an expansive ‘war machine’ that colonizes all places and flattens difference in the name of normative governance.